Young People’s View on Physical Activity - Kaupužs, Aivars; Ušča, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The habits of life obtained in period of youth may significantly affect health, development and quality of life in the future. The purpose of this qualitative study was to found out the thoughts and experience of physical activity in youth population. 30 young people aged 18 to 25 years of various activity levels provided semi-structured interviews with regard to personal experiences, barriers, and motives for physical activities. The sport trainings (team games, work out in the gym etc.) are more common associations for physical activity description than daily activities. The positive previous experience, the support from partner or friends and physical appearance are the most important factors for participation in sport activities. The most common barriers are time constraints and laziness.